External validation of molecular subtype classifications of colorectal cancer based on microsatellite instability, CIMP, BRAF and KRAS - Alwers, Elizabeth; Bläker, Hendrik; Walter, Viola; Jansen, Lina; Kloor, Matthias; Arnold, Alexander; Sieber-Frank, Julia; Herpel, Esther; Tagscherer, Katrin; Roth, Wilfried; Chang-Claude, Jenny; Brenner, Hermann; et al. (BMC cancer, 2019)
Competing molecular classification systems have been proposed to complement the TNM staging system for a better prediction of survival in colorectal cancer (CRC). However, validation studies are so far lacking. The aim of this study was to validate and extend previously published molecular classifications of CRC in a large independent cohort of CRC patients.